Strategic Growth and Sustanaible Development of the "Borovella" Plantation - Sawicki, Adrian (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
Borovella, a Croatian organic blueberry farm, aims to lead Croatia's organic sector and expand into the growing European market with a strategy for 2025–2030. The European blueberry market is projected to grow from €8.88 billion in 2024 to €12.40 billion by 2029, driven by demand for sustainable foods (Research and Markets, Data Insights Market). Borovella plans to boost production using Croatia's favourable climate and securing essential organic certifications for key EU markets like Germany and the Netherlands. To strengthen its brand, Borovella will diversify into organic jams, snacks, and eco-tourism experiences such as farm tours and workshops. Digital strategies, including e-commerce and social media, will enhance customer reach, while partnerships with retailers will increase product availability. With a focus on sustainability and innovation, Borovella is poised to lead Croatia's organic farming sector and set a standard in Europe's growing organic market.